Strategi Menjaga Ketahanan Industri Furnitur Jawa Tengah di Era Digitalisasi - Amelia, Reni; Mun'im, Akhmad (Politeknik Statistika STIS, 2024)
The era of the 4.0 industrial revolution is driving digitalization in the furniture industry, including the expansion of marketing through the internet. This study examines the impact of digitalization on the income of furniture industry entrepreneurs and the characteristics of those who adopt it in Central Java, using data from the National Labor Force Survey in August 2022. The results of the t-Student test show that entrepreneurs who utilize digitalization have higher average incomes. An association test also indicates a link between digitalization and income. The results of random undersampling and oversampling classification and regression trees identify two characteristics of furniture industry entrepreneurs who utilize digitalization: those who work with the help of permanent/paid workers, or work alone, or with the help of non-permanent/unpaid workers, and those from the Pre Boomers, Millennials, or Z generations. The proposed strategies to maintain the resilience of the furniture industry in Central Java in the digital era include improving digital literacy among entrepreneurs, especially for older individuals or those with limited access to technology.